Serum-Free Thyroxine Levels Were Associated with Pulmonary Hypertension and Pulmonary Artery Systolic Pressure in Euthyroid Patients with Coronary Artery Disease - Bingjie Wu; Jingjing Jiang; Minghui Gui; Lin Liu; Qiqige Aleteng; Shanshan Wang; Xiaojing Liu; Yan Ling; Xin Gao (International Journal of Endocrinology)
The aim of this study was to evaluate the association between thyroid hormone levels, pulmonary hypertension (PH), and pulmonary artery systolic pressure (PASP) in euthyroid patients with coronary artery disease (CAD). A cross-sectional study was conducted in individuals who underwent coronary angiography and were diagnosed as CAD from March 2013 to November 2013. 811 subjects (185 women and 626 men) were included in this study. PASP was measured by transthoracic Doppler echocardiography. 86 patients were diagnosed as PH and had significantly higher free thyroxine (FT4) levels than those without PH. Multiple logistic regression analysis demonstrated an independent association of FT4 levels with PH after adjustment of gender, age, body mass index, systolic blood pressure, left ventricular ejection fraction, hypertension, and medication use of calcium channel blockers, ACE inhibitors, angiotensin II receptor antagonists, and nitrates. Serum-free triiodothyronine (FT3) and thyroid-stimulating hormone (TSH) were not associated with PH. Furthermore, multivariate linear regression analysis showed that FT4 levels emerged as an independent predictor for PASP, while FT3 and TSH levels were not associated with PASP. Our study demonstrated that, in euthyroid patients with CAD, FT4 was an independent risk factor for PH, and FT4 levels were independently associated with PASP.